2017
DOI: 10.1177/2158244017737815
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Pokémon: Augmented Reality Is a Universal Design for Learning Tool

Abstract: The success of Pokémon Go is demonstrating that augmented reality (AR) is reaching the masses quickly and can be a robust tool to enhance student engagement and learning. Leveraging AR for instructional purposes has the potential to become a powerful medium for Universal Design for Learning (UDL) by providing new tools for multiple means of representation, action and expression, and engagement. One of the advantages of using AR applications and AR platforms is the ability to display context relevant digital in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 26 publications
0
28
0
4
Order By: Relevance
“…Furthermore, it is documented in the literature that students learn better when they are actively involved in the learning process [81]. Our results indicate that AR technologies can contribute towards this direction since they provide students with new ways of accessing and interacting with information (ibid).…”
Section: In What Ways Do the Affordances Provided By The Combination mentioning
confidence: 51%
See 1 more Smart Citation
“…Furthermore, it is documented in the literature that students learn better when they are actively involved in the learning process [81]. Our results indicate that AR technologies can contribute towards this direction since they provide students with new ways of accessing and interacting with information (ibid).…”
Section: In What Ways Do the Affordances Provided By The Combination mentioning
confidence: 51%
“…With regards to the third research question of this study, the results of the study indicated that the creation of a multimodal environment, which draws on the principles of UDL and combines the affordances of ARG-AR, can respond to the wide range of students' diverse needs. As other researchers have supported, AR technologies should be considered as contemporary resources that can be used in the context of the UDL framework and as powerful tools that teachers can exploit to build on the work they already do in the classroom [81]. The results indicated that all students participated in the activities and the degree of their engagement was higher in comparison to more conventional classroom activities.…”
Section: In What Ways Do the Affordances Provided By The Combination mentioning
confidence: 92%
“…Όσον αφορά την παιδαγωγική αξία των εφαρμογών της AR στον χώρο της ειδικής αγωγής και εκπαίδευσης, αν και βασίζονται τις αρχές του Καθολικού Σχεδιασμού για τη Μάθηση, έχουν δημοσιευτεί λίγες μελέτες που περιλαμβάνουν μαθητές με αναπηρίες, οι περισσότερες από τις οποίες έχουν πραγματοποιηθεί στο πλαίσιο της συνεκπαίδευσης (Mcmahon, 2014Quintero et al, 2019• Walker et al, 2017. Ο Quintero και οι συνεργάτες του (2019) κατά τη βιβλιογραφική ανασκόπηση 50 μελετών μεταξύ 2008 και 2018 για τη χρήση της AR σε περιβάλλοντα συνεκπαίδευσης κατέληξαν στο συμπέρασμα ότι μεταξύ των μεγαλύτερων πλεονεκτημάτων των εφαρμογών AR είναι η βελτίωση του επιπέδου κατανόησης και προσοχής από τους μαθητές με ΕΕΑ, η μείωση των οπτικών, ακουστικών ή κινητικών εμποδίων, η αυξανόμενη αναγνώριση της έκφρασης των συναισθημάτων, η μείωση των προβλημάτων ανάγνωσης, η πρόοδος σε θέματα λεξιλογίου, η ευκολία πρόσβασης σε πληροφορίες, η βελτίωση της πλοήγησης και της επικοινωνίας.…”
Section: εικόναunclassified
“…The term AR was introduced in 1992; however, examples of AR have existed since 1968, even though the technology available at the time was immovable, large, and expensive-much different from the affordable mobile devices, like smart phones and tablets, available today (Walker et al, 2017). The cognitive theory of multimedia learning is based on the principle that words and pictures are more effective for learning than words only (Mayer, 1997); AR overlays printed text, audios, videos, and other virtual content (Sommerauer & Müller, 2014).…”
mentioning
confidence: 99%
“…The cognitive theory of multimedia learning is based on the principle that words and pictures are more effective for learning than words only (Mayer, 1997); AR overlays printed text, audios, videos, and other virtual content (Sommerauer & Müller, 2014). AR can also function as an assistive technology and/or instructional technology; in accord with the principles of the universal design for learning, it can support students with disabilities in their learning process (Walker et al, 2017).…”
mentioning
confidence: 99%